A Comparison of 14 Erythrobacter Genomes Provides Insights into the Genomic Divergence and Scattered Distribution of Phototrophs - Zheng, Qiang; Lin, Wenxin; Liu, Yanting; Chen, Chang; Jiao, Nianzhi (Frontiers in Microbiology, 2016)
Aerobic anoxygenic phototrophic bacteria (AAPB) are bacteriochlorophyll a (Bchl a)-containing microbial functional population. Erythrobacter is the first genus that was identified to contain AAPB species. Here, we compared 14 Erythrobacter genomes: seven phototrophic strains and seven non- phototrophic strains. Interestingly, AAPB strains are scattered in this genus based on their phylogenetic relationships. All 14 strains could be clustered into three groups based on phylo-genomic analysis, average genomic nucleotide identity and the phylogeny of signature genes (16S rRNA and virB4 genes). The AAPB strains were distributed in three groups, and gain and loss of phototrophic genes co-occurred in the evolutionary history of the genus Erythrobacter. The organization and structure of photosynthesis gene clusters (PGCs) in seven AAPB genomes displayed high synteny of major regions except for few insertions. The 14 Erythrobacter genomes had a large range of genome sizes, from 2.72 to 3.60 M, and the sizes of the core and pan- genomes were 1,231 and 8,170 orthologous clusters, respectively. Integrative and conjugative elements (ICEs) were frequently identified in genomes we studied, which might play significant roles in shaping or contributing to the pan-genome of Erythrobacter. Our findings suggest the ongoing evolutionary divergence of Erythrobacter genomes and the scattered distribution characteristic of PGC.